Pengaruh Lokasi, Cita Rasa Dan Persepsi Harga Terhadap Keputusan Pembelian: (Studi Kasus Pada Es Teh Mbok Dhe Di Anjasmoro) - Kafy Nur Latief; Yani Prihati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study “aims to analyze the influence of location, taste, and price perception on purchasing decisions of consumers of Es Teh Mbok Dhe in Anjasmoro. The phenomenon of increasing contemporary beverage businesses has triggered intense competition, so it is important for business actors to understand the factors that influence consumer behavior. The method used in this study is a quantitative approach with multiple linear regression analysis techniques. Data were collected by distributing questionnaires to 100 respondents who are active consumers of Es Teh Mbok Dhe. The results of the analysis show that the variables of location, taste, and price perception simultaneously have a significant effect on purchasing decisions. Partially, each variable is also proven to have a significant positive effect on purchasing decisions. This finding implies that in order to increase consumer purchasing interest, business actors need to pay attention to strategic locations, maintain taste quality, and set affordable and competitive prices”